Students’ Mathematical Critical Thinking Skills and Self-Esteem as a Basis for PjBL–STEM - Cholifah; Nuriana Rachmani Dewi (Universitas Teknokrat Indonesia, 2026)
Mathematical critical thinking skills are essential 21st-century competencies that must be developed through mathematics learning. However, results from international and national assessments indicate that these skills remain low among junior high school students. This study aims to describe the mathematical critical thinking skills and self-esteem of eighth-grade students at SMP Negeri 10 Semarang as a basis for designing innovative learning using a Project-Based Learning (PjBL) model with a STEM approach assisted by flipbook-based media. This study employed a descriptive quantitative design involving 31 eighth-grade students. Data were collected through a mathematical critical thinking skills test and an interview with a mathematics teacher. The results showed that the average score of students’ mathematical critical thinking skills was 31.77, with most students categorized at a low level. Interview findings indicated that students’ self-esteem tended to be moderate to low, characterized by low confidence, passive participation, and reluctance to engage with non-routine problems. These findings highlight the need for learning designs that simultaneously address cognitive and affective aspects through flipbook-assisted PjBL–STEM learning.